Mengadap Rebab: Dewa Muda - Chong, Lee Suan; Azwan Abdul Karim; Mohammad Dzulsyafiq Mohammad (Universiti Malaysia Kelantan, 2016)
Dewa Muda tale tells about a young prince who searches for a princess to be his soul mate. The prince's father is Tok Raja Jiwa, and his mother is Puteri Selindung Bulan. The story recounts the difficulties, trials, and tribulations faced by Dewa Muda to meet Princess Ratna Mas in the heavens. It signifies the internal conflict within Dewa Muda to meet his beloved soul mate and this inner conflict delicately elucidates human lust.